The Correlation Between Listening to Dangdut Music and the Work Enthusiasm of Chili-Picking Laborers in Pojok Village, Ponggok District, Blitar Regency - Haryanti, Nik; Sakdiyah, Viya Ananda Nur (Universitas Islam Balitar, 2025)
This study aims to analyze the relationship between listening to dangdut music and the work enthusiasm of chili-picking laborers in Pojok Village, Ponggok District, Blitar Regency. The method used is quantitative with a correlational research design. The research population includes all chili-picking laborers in the village, and a random sample of 30 individuals was selected. Hypothesis testing was conducted using the product moment correlation test. The results show a positive relationship between listening to dangdut music and workers’ enthusiasm, with a correlation coefficient of r = 0.561, which is greater than the critical value of r table = 0.3061 at a 5% significance level. Given that the significance level of 0.000 is below the threshold of 0.05, the null hypothesis (H₀) is consequently rejected, and the alternative hypothesis (H₁) is accepted. This indicates that dangdut music influences the work enthusiasm of chili-picking laborers.